DINAMIKA AIR TANAH DAN INTER RELASINYA DENGAN AIR SUNGAI DI CEKUNGAN BANDUNG - Satrio Satrio (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2008)
At the present time, water scarcity in Bandung Basin has reached its critical point, marked with springs that stop discharging and lowering water table. The same condition can be seen on river water that heavily exposed by industrial waste along the river. Through environmental isotopes (2H, 18O and 14C) approach, the condition of deep and shallow groundwater wells alongside the river can be known. This research was conducted by taking some samples of shallow groundwater, deep groundwater and river water (Citarum, Cikapundung, Cikeruh and Citarik). The amount of water sample needed for 2H and 18O isotopes analysis was 20 ml, whereas for 14C isotope analysis, 60 liters of water sample needed to extract into BaCl3 precipitation. Based on isotopes 2H, 18O and graphic 2H vs 18O data show that there are three of resident groundwater (shallow groundwater) which its groundwater have been mixing by river water. Whereas the result of isotope 14C, does not show inter relation, either by shallow groundwater or river water. From iso-age contour, it could be concluded that the dynamics pattern of deep groundwater show movement derived from north and south mountains to north-west direction (Cimahi and Leuwigajah). These locations are industrial area with very high groundwater exploitation.